(untitled) - Graham, Ian (Wokingham, England, 1994)
A revision of Ian Graham's successful survey of the whole area of object technology. It covers object-oriented programming, object-oriented design, object-oriented analysis, object-oriented databases, and treats several related technologies. New to this edition are more applications of object-oriented methods and over twice the material on design and analysis.
Keywords: Object-oriented methods (Computer science),Lý thuyết lập trình